Exchange rate behavior in the cases of the Zambian Kwacha and Malawian Kwacha : is there misalignment?,Possible exchange rate misalignment : the cases of the Zambian Kwacha and Malawian Kwacha - Magwizi, Brenda Thandekha,Rhodes University (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2011)
The exchange rate is the price of one currency against another currency or currencies of a group of countries. Real exchange rates are important because they show the external competitiveness of a country"Ÿs economy. Thus, when the exchange rate of a country is misaligned, this will affect its trade, production and the welfare of people. This study analysed macroeconomic determinants of the real exchange rate and dynamic adjustment of the real exchange rate as a result of shocks to these determinants. The study also determined the extent of misalignment of the real exchange rate in Malawi and Zambia and identified variables that contributed to it. Such information is important to policy makers. Quarterly data were used for both countries from 1980:1-2008:4. The literature review identified those variables that determine the exchange rate and these include government consumption, foreign aid, net foreign assets, commodity prices, terms of trade, domestic credit, openness and the Balassa Samuelson effect (technological progress). To determine the long-run relationship between the exchange rate and its determinants, we employed the Johansen approach and the Vector Error Correction Model (VECM). For robustness check on the long-run and shortrun effects of determinants on the exchange rate, variance decomposition and impulse response analyses were used. Results in the study show that in Malawi for both models, an increase in LAID, LGCON and LTOT resulted in real exchange rate depreciation and increases in LDC, NFA and LNEER resulted in an appreciation. In Zambia, increases in LAID, LGCON, LOPEN and LTOT caused the real exchange rate to depreciate while increases in LDC, NFA and LCOPPER led to an appreciation. Lagged LREER and LNEER were found to have short run effects on the equilibrium exchange rate for Malawi and lagged LCOPPER and LDC for Zambia. Periods of exchange rate misalignment were found in both countries. It was also found that the coefficient of speed of adjustment in Malawi in models 1 and 2 indicate that 11% and 27% of the variation in the real exchange rate from its equilibrium adjust each quarter respectively. The speed of adjustment for Zambia in both models was 45% and 47% respectively, higher than that of Malawi. Foreign aid has proven to be important in exchange rate misalignment in both countries, though this was not really expected in the case of Zambia. Given these results, it may be of interest to policy makers to understand which variables impact most on the exchange rate and how misalignment due to these determinants can be minimised.
Keywords: Foreign exchange rates -- Zambia; Foreign exchange rates -- Malawi; International relations -- Case studies -- Zambia; International relations -- Case studies -- Malawi